Design and Implementation of ZigBee-Ontology-Based Exhibit Guidance and Recommendation System - Hung-Yu Chien; Shyr-Kuen Chen; Ching-Yang Lin; Jia-Ling Yan; Wei-Chen Liao; Huan-Yi Chu; Kuan-Ju Chen; Bo-Fan Lai; Yi-Ting Chen (International Journal of Distributed Sensor Networks)
Even though information devices and systems have been widely applied in guidance service for museums and exhibitions, there are still several critical requirements unsatisfied. In our research, we systematically examine the requirements and then propose a new architecture for museum/exhibition guidance service; we further, based on ZigBee and ontology, implemented a new guide device and a new guidance and recommendation system. The contributions include (1) an extendable and comprehensive architecture for guidance service; (2) an automatic and personalized guidance service system; (3) overcoming the limitations and weaknesses of conventional guidance systems short distance limitation and network saturation problem in crowded environments; and (4) on-line user status monitoring and real-time recommendation service.